1991
DOI: 10.1111/j.1600-0447.1991.tb03152.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between schizophrenics born in winter and summer

Abstract: A total of 1814 patients were studied from the Mississippi State Hospital with a DSM-III diagnosis of schizophrenia and aged 15-39 years at the time of admission. The 634 schizophrenics with a birth date between 1 December and 31 March were compared with the 1180 born between 1 April and 30 November for age of admission, race, sex, marital status, duration of initial admission and clinical subtype. The only significant difference between the variables was the duration of the first admission: winter-born patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In contrast, Watson et al [39] found winter birth excesses only among schizophrenics who had never married, a group that is thought to be more likely to have severe, process schizophrenia with poor premorbid history. Other studies [16,30,31] found no relationship between season of birth and a variety of clinical variables including age of onset, marital status, total duration of hospitalization, and number of readmissions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, Watson et al [39] found winter birth excesses only among schizophrenics who had never married, a group that is thought to be more likely to have severe, process schizophrenia with poor premorbid history. Other studies [16,30,31] found no relationship between season of birth and a variety of clinical variables including age of onset, marital status, total duration of hospitalization, and number of readmissions.…”
Section: Discussionmentioning
confidence: 91%
“…Data on clinical subtype are inconsistent as well. Three different studies [16,30,37] compared the birth seasons of paranoid and non-paranoid schizophrenics and found no significant differences between these two subtypes. In a much smaller study, Opler and Kay [26] found that all patients with positive syndrome schizophrenia (as defined by the PANSS) were born in nonwinter months, whereas equal numbers of negative syndrome patients were born in winter and non-winter months.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between season of birth, a variety of clinical variables including age of schizophrenia onset, marital status, total duration of hospitalization, and number of hospital admissions and prognosis has not yet been established, season of birth does appear to contribute to not only in the development but also the course of the disease for patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Later achievement of learning to stand or walk and becoming potty-trained were not associated with poorer outcome at 35 years (Jääskeläinen et al, 2008). Only pre-natal exposure to environmental adversities increased the risk of re-hospitalization (Levine et al, 2014) and patients born in winter have had shorter periods of psychiatric hospitalization during first admission (Rodrigo et al, 1991). Comparative studies on developmental and environmental predictors of outcomes in schizophrenia and individuals without schizophrenia, are also lacking.…”
Section: Introductionmentioning
confidence: 98%